Decreases of Blood Oxygenation Level—Dependent Signal in the Activated Motor Cortex during Functional Recovery after Resection of a Glioma - Murata, Yoshihiro; Sakatani, Kaoru; Katayama, Yoichi; Fujiwara, Norio; Hoshino, Tatsuya; Fukaya, Chikashi; Yamamoto, Takamitsu (American Journal of Neuroradiology, 2004)
Summary: The present case demonstrates that the blood oxygenation level—dependent (BOLD) signal intensity can decrease in the activated motor cortex on the lesion side (left) of a patient with a left frontal glioma during functional recovery after surgery. Near-infrared spectroscopy revealed that the decrease of BOLD signal was associated with increases of cerebral blood volume and deoxyhemoglobin concentrations in the cerebral vessels. This implies that the interpretation of results obtained by functional MR imaging in patients with brain disorders must take into consideration such atypically evoked cerebral blood oxygenation changes, which do not increase the BOLD signals.